PENERAPAN AUDIT OPERASIONAL UNTUK EVALUASI EFEKTIVITAS DAN EFISIENSI RESTO “X” DI SURABAYA - Ellena Pratiwi Tirtoatmojo; Eko Pudjolaksono (Perpustakaan Universitas Surabaya, 2018)
The growth of economic accompanied by spending on food and beverage consumption. This opportunity makes restaurant businesses growing rapidly. The purpose of every business entity is to gain profit to develop and maintain their existences. Its causes the revenue cycle becomes one of the most important things and need operational audit to be more effective and efficient. Business entity that becomes the object is Resto “X that sells Chinese food and seafood. The scope of this research is revenue cycle for dine in activity with data from August until November 2017. The aims is to explanatory, researcher is trying to find existing problems and its solutions that can improve the effectiveness and efficiency of revenue cycle. Researcher using interview method, observation, and analysis document to get information. The result is the Resto “X” need to do separation of cash receipt function and accounting, setting goals progressively, and assigning responsibility for every waiter or waitress. In generally, revenue cycle is quite effective and efficient but there are some weaknesses that need to be repaired. The improvement is aimed to makes Resto “X” able to achieve its objectives more effectively and efficiently.